2013
DOI: 10.3892/or.2013.2474
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced autophagic flux by endoplasmic reticulum stress in human hepatocellular carcinoma cells contributes to the maintenance of cell viability

Abstract: Abstract. Endoplasmic reticulum (ER) stress and autophagy are important adaptive responses in eukaryotes. The aim of this study was to investigate the autophagic responses in hepatocellular carcinoma (HCC) cells under ER stress and the effect of autophagy on cell survival and death. The human HCC cell line HepG2 was stimulated with tunicamycin to induce ER stress. Cell viability was detected using the Cell Counting Kit-8. The accumulation of autophagic compartments was observed using transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…ER stress is able to induce autophagy [ 21 ], which has been shown to protect against hepatocarcinogenesis [ 22 ]. We therefore tested whether TUDCA modulates autophagy in vivo ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…ER stress is able to induce autophagy [ 21 ], which has been shown to protect against hepatocarcinogenesis [ 22 ]. We therefore tested whether TUDCA modulates autophagy in vivo ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…R corresponds to the addition of an arginine during the fusion whereas Q corresponds to the addition of a glutamine. Of the five SNAREs detected, only one corresponds to a Q-SNARE as observed in other cell types [122,123] (Fig. 1, indicated by a star).…”
Section: A Proteome Indicating a Proximity With The Endomembrane Systemmentioning
confidence: 96%
“…Although autophagy seems to play dual role on determining cell's fate according to the extent of ER stress [36], accumulated evidences suggest autophagy induction contributes to protect several types of cells from ER stress [37][38][39][40]. Ma et al (2013) reported that pretreatment with 3-methyladenine, which blocks initiation of autophagic vesicles, accelerates Tmmediated cytotoxicity of HepG2 cells [37].…”
Section: Accepted Manuscriptmentioning
confidence: 99%